Design and synthesis of new 1-alkyl-3-butylimidazolium bromide ionic liquids as media for DNA solvation - Jumbri, Khairulazhar (2015)
The influence of ionic liquids (ILs) on the structural properties of DNA was revealed by experimental and molecular dynamics (MD) simulation. In the first part of experimental section, six new 1-alkyl-3-butylimidazolium bromide ILs ([Cnbim][Br] where n = 2, 4, 6, 8, 10 and 12) were successfully synthesized. All of the ILs was obtained using simple alkylation reaction of 1-butylimidazole with various bromoalkanes, which gave high yield above 85%. Their physico-chemical properties, including the spectroscopic characteristics have been comprehensively studied. Three of these ILs (C2, C4, C6) exist in liquid form while the others appear as semi solid at room temperature. Proton and carbon NMR and CHN elemental analysis were carried out to identify the molecular structure and purity of ILs produced. The thermal stability studied using TGA indicated that these new ILs were stable up to 270°C. As expected, the viscosity of three liquid salts hugely increased from 199 mPa·s ([C2bim][Br]) to 1180 mPa·s ([C6bim][Br]), while the density slightly decreased with increasing length of alkyl chains. The properties of Calf thymus DNA in hydrated ILs were studied using spectroscopic analysis. The strong interactions between the P-O bond of DNA phosphate groups and the [Cnbim]+ lead to compact DNA conformation, which excludes the intercalation of ethidium with DNA. Although the DNA stability is mainly due to the electrostatic attraction between DNA and ILs’ cation, hydrophobic interactions between hydrocarbon chains of [Cnbim]+ and DNA bases also provided a major driving force for the binding of ILs to DNA. The effect of ILs concentration at 25°C shows that the DNA maintains its B-conformation in all solution of hydrated ILs despite the high concentration up to 75% (w/w). During heating process, hydrated ILs are observed to stabilize DNA helical structure up to 56°C ± 1.0°C, almost 11°C higher than DNA in water. The DNA melting temperature is found gradually increases with increasing length of alkyl chain from 56°C ± 1.0°C (in [C2bim][Br]) to 58°C ± 1.0°C in the presence of [C6bim][Br]. In the first part of MD simulation, the force fields (FFs) parameter for these three liquid ILs ([Cnbim][Br] where n = 2, 4 and 6) was validated based on experimental evidences. The modified collision parameter (ζ) to 0.369 nm for the anion shows the simulation data obtained were in agreement with experimental density and viscosity with the percentage error below ± 2.0% and ± 10.0%, respectively. The validated FFs were then applied for simulation of DNA in these ILs. The MD data offers clear evidence that the DNA maintains its B-conformation in all [C4bim]Br systems (25, 50 and 75% w/w). The hydration layer around the DNA phosphate group was the main factor in determining DNA stabilization. Stronger hydration shells in 25% [C4bim][Br] in water (w/w) reduced the binding ability of ILs’ cations to the DNA phosphate groups. The computed energy shows that the electrostatic energy between [C4bim]+–[PO4]- (-46.55 ± 4.75 kcal mol-1) is lower than water–[PO4]-(-12.78 ± 2.12 kcal mol-1). Effect of temperature revealed that ILs was able to retain DNA native conformation at high temperature up to 373.15 K in the presence of 75% [C4bim]Br. All the simulations findings were in agreement with experimental evidences. The prediction solvation free energy of nucleic acids bases performed in last part of MD simulation revealed that the nucleic acid bases were better solvated in ILs rather than in aqueous solution.